2023
DOI: 10.1128/msystems.01282-22
|View full text |Cite
|
Sign up to set email alerts
|

CrAssphage May Be Viable Markers of Contamination in Pristine and Contaminated River Water

Abstract: Rivers support substantial populations and provide important ecosystem services. Despite the application of fecal coliform tests and other markers, we lack rapid and reproducible approaches for determining fecal contamination in rivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The negative samples in the current study may contain lower concentrations of crAssphage below the limits of detection. Lastly, new research has demonstrated the great diversity of crAss-like phages that can affect the detection of target genes using PCR [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative samples in the current study may contain lower concentrations of crAssphage below the limits of detection. Lastly, new research has demonstrated the great diversity of crAss-like phages that can affect the detection of target genes using PCR [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A specific group of bacteriophages named crAssphages have been proposed as potential universal human feces viral indicators in water bodies (Farkas et al, 2019;Mafumo et al, 2023). CrAssphages were described by Dutilh et al (2014) as the most abundant phages in the human gut virome.…”
Section: Bacteriophages As Pollution Indicators In Watermentioning
confidence: 99%
“…Further studies identified that crAssphages are highly specific and abundant to human feces (Sabar et al, 2022), highly prevalent in sewage samples (Stachler et al, 2017), and maintain correlation to the presence of human enteric viruses in water (Jennings et al, 2020). Given the previous characteristics, crAssphages have been preconized in favor of currently used fecal indicator bacteria (FIB), which poorly explain viral pathogen dynamics in water and have low host specificity, making difficult the identification of the source of contamination (Ward et al, 2020;Toribio-Avedillo et al, 2021;Mafumo et al, 2023). CrAssphage applicability has been evaluated in several countries (Crank et al, 2020;Ward et al, 2020;Sangkaew et al, 2021;Nam et al, 2022) and shows promising possibilities for human fecal contamination detection in freshwater.…”
Section: Bacteriophages As Pollution Indicators In Watermentioning
confidence: 99%
“…Even though treated water samples tested negative for the presence of E. coli and total coliforms, these outbreaks raised questions about the sole usefulness of the current microbial standards of aquatic health for routine wastewater quality testing. Aside from Norovirus outbreaks, there are many other reports on Rotavirus, crAssphage, and Adenovirus prevalence in freshwaters (Hellmer et al, 2014; Garcia et al, 2022; Mafumo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%